2014
DOI: 10.1158/1078-0432.ccr-14-0392
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Dose-Finding Study of the Novel Toll-like Receptor 8 Agonist VTX-2337 in Adult Subjects with Advanced Solid Tumors or Lymphoma

Abstract: Purpose: This phase I, open-label, uncontrolled, ascending-dose study explored the safety, maximum tolerated dose (MTD), pharmacokinetics, and pharmacology of the TLR8 agonist VTX-2337 in subjects with advanced solid tumors or lymphoma.Experimental Design: VTX-2337 doses (0.1-3.9 mg/m 2 ) were administered subcutaneously on days 1, 8, and 15 of each 28-day cycle. Safety/tolerability assessments included adverse events (AE); physical, ophthalmologic, and laboratory evaluations; and electrocardiograms. Dose-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 23 publications
1
44
0
1
Order By: Relevance
“…In this initial clinical study, the safety, MTD, PK, and PD activity of motolimod were assessed in a small number of subjects with advanced solid tumors. Although the study was not designed to demonstrate efficacy, multiple subjects had evidence of clinical benefit (10), and motolimod has been subsequently assessed for efficacy in multiple clinical studies, including ongoing phase II, randomized placebo controlled studies, in ovarian cancer and SCCHN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this initial clinical study, the safety, MTD, PK, and PD activity of motolimod were assessed in a small number of subjects with advanced solid tumors. Although the study was not designed to demonstrate efficacy, multiple subjects had evidence of clinical benefit (10), and motolimod has been subsequently assessed for efficacy in multiple clinical studies, including ongoing phase II, randomized placebo controlled studies, in ovarian cancer and SCCHN.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three subjects were evaluated in 8 successive cohorts using a dose-ascending protocol, where motolimod was administered weekly via s.c. injection, with weekly doses ranging from 0.1 to 3.9 mg/m 2 . Motolimod was well tolerated, with the predominant adverse events (AE) being transient grade 1 or 2 fever, chills, flu-like symptoms, and injection site reactions (10). The 3 highest motolimod dose levels; 2.0, 2.8, and 3.9 mg/m 2 (cohorts 6-8) administered weekly, were both active and tolerated.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Imiquimod (Aldara; Graceway Pharmaceuticals), a TLR7 and TLR8 agonist, has been approved as a topical monotherapy for the treatment of basal cell carcinoma 59 . Small-molecule agonists of TLR7 (852A) 60 and TLR8 (VTX-2337) 61 suitable for systemic administration are being evaluated as single agents in both solid and haematological malignancies. TLR9 agonists, such as IMO-2055, CPG 7909 and MGN1703, induce type l IFN secretion in dendritic cells, promoting a T H 1-type response of cytotoxic dendritic cells, natural killer cells and T cells as well as promoting M2 to M1 switching 133 ; all these effects contribute to tumour-specific immune responses and the reversal of immune suppression.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…VTX-2337 is a synthetic TLR8 agonist that demonstrated effectiveness in preclinical models of head and neck cancer through innate immune modulation (Stephenson, et al, 2013). Subsequent phase I dose escalation studies demonstrated safety in patients with advanced cancer (Dietsch, et al, 2015;Northfelt, et al, 2014). However, clinical benefit of this strategy is currently unproven and concerns regarding off-target effects persist.…”
Section: Modulators Of Innate Immunitymentioning
confidence: 99%